The Takeover and Selection Effects of Foreign Ownership in Germany : An Analysis Using Linked Worker-Firm Data - Martyn J. Andrews; Lutz Bellmann; Thorsten Schank; Richard Upward (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2007)
We use a linked employer-employee data set from Germany to estimate the wage effect of foreign-affiliates in East and West Germany. In addition, the wage effects of the large number of West German affiliates which are located in East Germany are also considered. The implemented techniques allow us to control both for worker- and plant-level unobserved components of earnings. We find large selection effects both in terms of worker and firm unobserved components of wages. The selection effect is larger for East German plants. Once it is taken into account, the genuine takeover effect is small and in some cases insignificantly different from zero. In contrast to the selection effect, the takeover effect is slightly larger in West Germany, where it amounts to 2.7 %. – – Mit einem deutschen kombinierten Betriebs-Beschäftigten-Datensatz wird analysiert, ob Betriebe im ausländischen Eigentum höhere Löhne zahlen. Auch werden Lohndifferentiale von ostdeutschen Betrieben in westdeutschem Eigentum untersucht. Die verwendeten Schätzmethoden erlauben es, für jeweils unbeobachtbare Personen- und Betriebsheterogenitäten zu kontrollieren. Bezüglich beider Komponenten werden große Selektionseffekte gefunden, wobei diese für ostdeutsche Betriebe größer sind. Der verbleibende (wahre) Übernahmeeffekt ist gering und teilweise nicht signifikant von Null verschieden. Im Gegensatz zum Selektionseffekt ist der Übernahmeeffekt etwas größer für Westdeutschland, wo er 2,7% beträgt.
Keywords: C21; J31; F23; 330; foreign ownership; wages; linked employer-employee data; Lohnstruktur; Eigentümerstruktur; Multinationales Unternehmen; Deutschland; Alte Bundesländer; Neue Bundesländer